Confined and interface phonons in combined cylindrical nanoheterosystem - Makhanets, O.M.; Voitsekhivska, O.M.; Gryschyk, A.M. (Condensed Matter Physics, 2006)
The spectra of all types of phonons existing in a complicated combined nanoheterosystem consisting of three cylindrical quantum dots embedded into the cylindrical quantum wire placed into vacuum are studied within the dielectric continuum model. It is shown that there are confined optical (LO) and interface phonons of two types: top surface optical (TSO) and side surface optical (SSO) modes of vibration in such a nanosystem. The dependences of phonon energies on the quasiwave numbers and geometrical parameters of quantum dots are investigated and analysed.